Desafios e estratégia de permanência das estudantes negras cotistas do curso de Serviço Social da Universidade Federal de Sergipe (UFS) - Guimarães, Rosane Amália de Jesus (2024)
This research aimed to find out what are the challenges and strategies for the permanence of black quota students after entering the Federal University of Sergipe (UFS), taking into account the 10 years since the Quota Law was established and taking into consideration the Student Assistance Policy. of this same University. For this purpose, the population was comprised of black female students enrolled in the UFS Social Service Course with active enrollment between the years 2012 and 2022. Among these, the sample consists of 15 students who were assisted by some aid and/or scholarship financed by the National Student Assistance Program (PNAES). In addition to empirical research, I used both bibliographic and documentary research. I was able to see that although Student Assistance is extremely important for the permanence of students, especially quota holders, it still leaves something to be desired in terms of its coverage, not reaching a considerable number of them. Furthermore, the values of Aid and/or Scholarships differ from the current reality of the country. This even means that our students have to take part in other paid activities to actually be able to stay at the University, which ends up limiting their academic performance as they are unable to dedicate themselves exclusively to their studies. The fact that the University does not have specific policies for quota students often ends up not allowing them to access assistance actions - including the university tripod which is also financed by PNAES resources. Thus, in addition to a detailed look at quota students in general, there is an urgent need to look at women quota students who, in addition to the race and class prejudices suffered, go through the effects of sexism caused by patriarchy, historically becoming much more fragile and hit by obstacles when it comes to being able to stay and complete a higher education course.